Endogenous erythropoietin has immunoregulatory functions that limit the expression of autoimmune kidney disease in mice - Bin, Sofia; Cantarelli, Chiara; Horwitz, Julian K.; Gentile, Micaela; Podestà, Manuel Alfredo; La Manna, Gaetano; Heeger, Peter S.; Cravedi, Paolo (Frontiers in Immunology, 2023)
Background: Administration of recombinant erythropoietin (EPO), a kidney-produced hormone with erythropoietic functions, has been shown to have multiple immunoregulatory effects in mice and humans, but whether physiological levels of EPO regulate immune function in vivo has not been previously evaluated.We generated mice in which we could downregulate EPO production using a doxycycline (DOX)-inducible, EPO-specific silencing RNA (shEPOrtTA POS ) and we crossed them with B6.MRL-Fas lpr /J mice that develop spontaneous lupus. We treated these B6.MRL/lpr shEPOrtTA POS with DOX, and serially measured anti-dsDNA antibodies, analyzed immune subsets by flow cytometry and evaluated clinical signs of disease activity over 6 months of age in B6.MRL/lpr shEPOrtTA POS and in congenic shEPOrtTA NEG controls.Results: In B6.MRL/lpr mice, Epo downregulation augmented anti-dsDNA autoantibody levels, increased disease severity and percentages of germinal center B cells compared to controls. It also increased intracellular levels of IL-6 and MCP-1 in macrophages.Discussion: Our data in a murine model of lupus document that endogenous EPO reduces T and B cell activation and autoantibody production, supporting the conclusion that EPO physiologically acts as a counterregulatory mechanism to control immune homeostasis.